Different degree of cooperativity in adult, embryonic and mutated mouse muscle nicotinic receptors - Krùsek, J; Vyskocil, F (Biochimica et biophysica acta, 2003)
Adult and embryonic nicotinic receptors expressed in COS cells have similar affinities for acetylcholine but differ in their Hill coefficient. Parameters of wild-type receptors were compared with those of receptors with mutated delta and gamma subunits in selected negatively charged amino acids, which were expected to participate in agonist binding. A tentative scheme of affinities, allosteric interactions and channel gating efficacy was used for assessing the role of mutated amino acids in the channel function. In three models, the parameters of wild-type embryonic and adult receptors were compared with those of receptors with mutated delta and gamma subunits. The analysis of different models of channel activation indicates that negatively charged amino acids which were mutated in the delta subunit in embryonic receptors participate in channel gating and in allosteric interactions between subunits rather than directly in agonist binding. Changes in the gamma subunit in the embryonic receptors and delta subunit in the adult receptors could equally affect agonist binding, allosteric coupling between subunits or channel gating.
Keywords: Acetylcholine; acetylcholin; Muscle, Skeletal; Point Mutation; Mice; genetické vektory; bodová mutace; Cloning, Molecular; COS buňky; chemické modely; Genetic Vectors; nikotinové receptory; zvířata; Binding Sites; kosterní svaly; Receptors, Nicotinic; klonování DNA; myši; Models, Chemical; vazebná místa; COS Cells; Animals